Treatment of Shallow Groundwater Quality for Non-potable Use: A Case Study in Parit Raja, Batu Pahat, Johor - Mohd Shahli, Fitryaliah; Nazahiyah Rahmat, Siti; Nor Aishah Mohd Salleh, Siti; Ayob, Syafiqa (International Journal of Engineering and Technology, 2018)
Groundwater becomes an alternative water resource to meet up the demand of clean water in our country. Unfortunately, several contaminants could present in groundwater make it unsafe for domestic used and drinking water purpose. Therefore, groundwater should be treated to acceptable level before it can be consumed for further use. The aim of this study was to improve the groundwater quality in terms of physical parameters and bring it within the acceptable level using simple and economical aeration and filtration methods. Gravel, ceramic and charcoal were used as filter materials. The removal efficiency was determined from the calculated percentage removal of the tested parameters. Based on the results, groundwater showed improvement in its physical quality with percentage removal of turbidity, BOD and COD at 92%, 73% and 79%, respectively. Parameter pH also showed good improvement from slightly acidic to neutral range. However, TDS gave different results. With the exception of TDS, all parameters comply with the Malaysiaâ€™s standard of raw and drinking water quality set by Ministry of Health.Â Â